A new paradigm in postoperative colorectal cancer surveillance: integrating advanced imaging and multi-omics - Yu, Dongxue; Tai, Jiandong (Frontiers in Physiology, 2026)
Up to one-third of patients with localized colorectal cancer (CRC) relapse after curative-intent resection, as conventional markers like carcinoembryonic antigen (CEA) and scheduled CT/MRI often fail to detect micro-metastatic disease early. Advanced imaging, particularly radiomics, and liquid biopsy with circulating tumor DNA (ctDNA) are emerging as complementary tools to address this challenge. Radiomics extracts high-throughput image features to quantify risk and track response, with reported AUCs often ranging from 0.70 to 0.85. Concurrently, ctDNA has proven to be the strongest postoperative prognostic marker for recurrence in stage II-III CRC, providing surveillance lead times of 3–11 months over conventional methods. The landmark DYNAMIC trial demonstrated that ctDNA-guided adjuvant therapy safely reduced chemotherapy uses without compromising survival. By integrating ctDNA’s temporal “signal” with imaging’s spatial “localization,” clinicians can accelerate the detection of oligometastatic relapse, personalize surveillance, and refine treatment monitoring. This review synthesizes the evidence supporting this integrated approach, outlining the path toward a proactive, precision-based standard of care in postoperative CRC management, while also addressing the key challenges of standardization and clinical validation that must be overcome.